Analisis Prosedur Akuntansi Pengadaan Barang dan Jasa di Dinas Sosial Provinsi Sumatera Utara - Daffa Roghib; Aqwa Naser Daulay (BADAN PENERBIT STIEPARI PRESS, 2024)
Every agency needs good systems and procedures to help carry out direct shopping operational activities, one of which is shopping for goods and services. Procurement of goods and services greatly influences the running of private and government agencies and the success of a company. This research aims to analyze the systems and procedures for purchasing goods and services at the Regional Social Service of North Sumatra Province in accordance with applicable regulations. This type of research uses qualitative research with a descriptive analysis approach. The data collection methods used were interviews and documentation. The results of this research are that the systems and procedures for procurement of goods and services at the North Sumatra Province Social Service are running well and in accordance with Minister of Home Affairs Regulation No. 77 of 2020 concerning Technical Guidelines for Regional Financial Management. The North Sumatra Provincial Social Service has recorded using a computerized system which is recorded in the SIMDA application and has used accrual-based recording.